Postural stability and the influence of concurrent muscle activation: beneficial effects of jaw and fist clenching - Ringhof, Steffen; Leibold, Timo; Hellmann, Daniel; Stein, Thorsten (Gait & posture, 2015)
Recent studies reported on the potential benefits of submaximum clenching of the jaw on human postural control in upright unperturbed stance. However, it remained unclear whether these effects might also be observed among active controls. The purpose of the present study, therefore, was to comparatively examine the influence of concurrent muscle activation in terms of submaximum clenching of the jaw and submaximum clenching of the fists on postural stability. Posturographic analyses were conducted with 17 healthy young adults on firm and foam surfaces while either clenching the jaw (JAW) or clenching the fists (FIST), whereas habitual standing served as the control condition (CON). Both submaximum tasks were performed at 25% maximum voluntary contraction, assessed, and visualized in real time by means of electromyography. Statistical analyses revealed that center of pressure (COP) displacements were significantly reduced during JAW and FIST, but with no differences between both concurrent clenching activities. Further, a significant increase in COP displacements was observed for the foam as compared to the firm condition. The results showed that concurrent muscle activation significantly improved postural stability compared with habitual standing, and thus emphasize the beneficial effects of jaw and fist clenching for static postural control. It is suggested that concurrent activities contribute to the facilitation of human motor excitability, finally increasing the neural drive to the distal muscles. Future studies should evaluate whether elderly or patients with compromised postural control might benefit from these physiological responses, e.g., in the form of a reduced risk of falling.
Gesehen am 25.06.2020